The Miserable Mill: A Series of Unfortunate Events: Book 4 - Snicket, Lemony (U.S.A., 2000)
Accidents, evil plots, and general misfortune abound when, in their continuing search for a home, the Beaudelaire orphans are sent to live and work in a sinister lumber mill.
Keywords: Brothers and sisters -- Juvenile fiction; Juvenile fiction; Orphans -- Juvenile fiction